Autophagy is activated and involved in cell death with participation of cathepsins during stress-induced microspore embryogenesis in barley. (4th January 2018) - Bárány, Ivett; Berenguer, Eduardo; Solís, María-Teresa; Pérez-Pérez, Yolanda; Santamaría, M Estrella; Crespo, José Luis; Risueño, María C; Díaz, Isabel; Testillano, Pilar S
Abstract : Autophagy is activated and plays a role in stress-induced cell death during microspore embryogenesis, along with cathepsin-like C1A protease activities. Autophagy inhibition reduces cell death, improving embryogenesis induction efficiency. abstract: Microspores are reprogrammed towards embryogenesis by stress. Many microspores die after this stress, limiting the efficiency of microspore embryogenesis. Autophagy is a degradation pathway that plays critical roles in stress response and cell death. In animals, cathepsins have an integral role in autophagy by degrading autophagic material; less is known in plants. Plant cathepsins are papain-like C1A cysteine proteases involved in many physiological processes, including programmed cell death. We have analysed the involvement of autophagy in cell death, in relation to cathepsin activation, during stress-induced microspore embryogenesis in Hordeum vulgare . After stress, reactive oxygen species (ROS) and cell death increased and autophagy was activated, including HvATG5 and HvATG6 up-regulation and increase of ATG5, ATG8, and autophagosomes. Concomitantly, cathepsin L/F-, B-, and H-like activities were induced, cathepsin-like genes HvPap-1 and HvPap-6 were up-regulated, and HvPap-1, HvPap-6, and HvPap-19 proteins increased and localized in the cytoplasm, resembling autophagy structures. Inhibitors of autophagy and cysteine proteases reduced cell death and promoted embryogenesis. The findings reveal a role for autophagy in stress-induced cell death during microspore embryogenesis, and the participation of cathepsins. Similar patterns of activation, expression, and localization suggest a possible connection between cathepsins and autophagy. The results open up new possibilities to enhance microspore embryogenesis efficiency with autophagy and/or cysteine protease modulators.